Distribution analysis, updated checklist, and DNA barcodes of the endemic vascular flora of the Altai mountains, a Siberian biodiversity hotspot. Issue 1 (31st December 2022) - Erst, A.S.; Nikulin, A.YU.; Nikulin, V.YU.; Ebel, A.L.; Zibzeev, E.V.; Sharples, M.T.; Baasanmunkh, S.; Choi, Hyeok JAE; Olonova, M.V.; Pyak, A.I.; Gureyeva, I.I.; Erst, T.V.; et al.
Abstract : The Altai Mountains of central Asia are biologically rich and comprise a wide diversity of ecosystems and lineages, including numerous endemic vascular plant species. Here we provide an updated checklist of the endemic vascular flora of the Altai Mountains with more taxa and higher geographic resolution than previously reported, as well as first molecular data and specimen images for many of these species. This flora is now known to contain 321 endemic species distributed in 34 families, many of which are narrowly restricted to one subregion of the Altai. The Fabaceae has given rise to the most endemic species in the Altai (74 spp.), and most of this diversity is found in the large and ecologically important genera Astragalus and Oxytropis . Approximately 60% of the endemic flora was imaged and successfully barcoded with at least one of three common DNA barcoding loci, and a phylogenetic tree based upon these loci is also presented to display the evolutionary breadth of endemism in the Altai. The distribution of each endemic species is presented in terms of a standard geographic subdivision of the Altai region, with general conservation priorities discussed based on areas currently afforded protected status.